Early warning system-related challenges in health sector: A qualitative content analysis study in Iran - Seyed Hossein Hosseini; Hamid Reza Khankeh; Mehrdad Farrokhi; Mohammad Ali Hosseini; Pirhossein Koolivand; Mohammad Raeiszadeh (Wolters Kluwer Medknow Publications, 2020)
CONTEXT: Iran's health system has always faced many challenges in the field of disaster risk management. The establishment of early warning systems in countries has been identified as an important component of preparedness and risk reduction. AIMS: This study aims to extract the experiences of those involved in the field of risk management in relation to the challenges and problems of early warning system establishment in the Iran's health system. SUBJECTS AND METHODS: This was a qualitative study, which has been conducted using a content analysis method. Data were collected through semi-structured interviews with 16 individuals who had at least one disaster management experience at the emergency operation centers. Sampling was done purposefully. The data were then analyzed using the Grenheim method. RESULTS: Nine subcategories of data were analyzed that included legal vacancies, challenges related to protocols and guidelines, weaknesses in the prediction infrastructure, weaknesses in the communication infrastructure, poor coordination, scarcity of resources, inadequate education, information management challenge, and evaluation challenge, and three main categories were extracted that included policy challenges, infrastructure challenges, and management challenges that represented the issues experienced in establishing an early warning system in the Iranian health system. CONCLUSION: Policy-makers and managers of health system need to pay special attention to improve the legal framework and standard protocol, strengthening infrastructures, increasing management performance in the field of coordination, education, allocation of resources, flow of information, and evaluation system.